Human body - Rogers, Simon; Grundy, Peter (Somerville, Massachusetts Big Picture Press, an imprint of Candlewick Press, 2014)
Provides an easy-reference, graphically illustrated introduction to the human body and how it functions to sustain life, including digestion, reproduction, and the senses. -- Source other than Library of Congress.
The senses -- Reproduction -- The heart -- The brain -- Digestion -- The skeleton -- Human factory.
"Understand the facts in the blink of an eye"--Cover.
Keywords: Human physiology -- Juvenile literature; Human body -- Juvenile literature; Human anatomy -- Juvenile literature; Human physiology; Human body; Human anatomy